What's So Funny? Laughter in Shota Rustaveli’s The Man in the Panther’s Skin and the Romances of Chrétien de Troyes - Newell, Sally (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2019)
In a conference paper on good and bad speech in The Man in the Panther's Skin and the romances of Chretien de Toyes, I included a short segment on laughter, more for helpful suggestions from the audience than because I had insight into its occurrence in the literature. In the absence of any suggestions, I remained stymied for some time before finding sources that would lead to understanding. The purpose of this paper is to analyze episodes of laughter from the perspective of modern studies of the psychology of laughter and from the ethical views of Plato and Aristotle.